Physical Analysis In Making Rowe Pakoda: A Case Study Of Sumba Local Food Wisdom - Desak Made Anggraeni; Aurelia Astrid L. Jewaru (International Journal of Science, Technology and Applications, 2025)
This study aims to analyze the underlying physical principles of Rowe pakoda, a traditional snack from Sumba, using a case study approach grounded in local wisdom. A qualitative method was employed in this research, with data collected through participatory observation and in-depth interviews. The results indicate that the final quality of the product is significantly determined by the application of applied physics. The boiling process involves thermodynamic mechanisms, in which convective heat transfer and thermal hydration are the key drivers of starch gelatinization, resulting in a smooth texture and cohesion among the raw material components. Furthermore, fluid mechanics plays a role in analyzing the rheology of non-Newtonian dough, which regulates water absorption kinetics and product consistency stability. The findings validate that traditional Sumba cooking techniques are an intuitive and effective application of physical laws, providing a scientific contribution to the optimization of Indonesian archipelago cuisine. The novelty of this research lies in its systematic deconstruction of intuitive indigenous techniques into measurable scientific parameters, specifically by establishing a link between ancestral cooking methods and modern rheological models. This study moves beyond cultural documentation, providing a transformative framework that positions traditional Sumba cuisine as a precursor to contemporary food engineering and sustainable culinary optimization